Cementing material containing clay mineral
By using clay minerals, flue gas desulfurization by-products and converter steel slag in gelling materials, combined with improved agents, the utilization rate of clay minerals and the compressive strength of gelling materials are improved, and clay minerals in concrete and filling materials are solved. Insert performance problems and reduces filling mining costs.
Patent Information
- Application Number
- CN202411271778.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
When using sand and gravel aggregates in concrete and filling materials, the high content of clay minerals will reduce compressive strength and increase resource waste, and the high price of cement leads to increased filling costs. It is necessary to find suitable alternative materials to reduce mining costs. .
A cementitious material containing clay minerals is used, and the composition includes clay minerals, flue gas desulfurization by-products, converter steel slag and improved agents. The modified agents include calcium silicate, tricalcium aluminate, nano-alumina trioxide, tricalcium silicate , tetracalcium ferroaluminate, methyl polycarboxylic acid and vinyl acetate, improve the uniformity and cementing properties of the material by defining the particle size and water cementing ratio of clay minerals.
It significantly reduces the cost of raw materials, improves the utilization rate of clay minerals and the compressive strength of gelled materials, solves the problem of clay mineral storage, and reduces the cost of filling mining.
Smart Images

Figure BDA0005038926560000031 
Figure BDA0005038926560000041 
Figure BDA0005038926560000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementitious materials, and in particular to a cementitious material containing clay minerals. Background Art
[0002] Clay minerals are layered silicate minerals with a particle size of less than 2μm. They are also one of the main components of soil. Their types and content will greatly affect the performance of soil. In the manufacturing process of concrete and filling materials, sand and gravel are needed as aggregates. During the formation or mining and crushing process of sand and gravel aggregates, clay minerals are attached to the surface, which will have an adverse effect on the various properties of concrete and filling materials. With the increase of kaolinite, montmorillonite and illite content in clay minerals, the compressive strength of concrete and filling materials will be significantly reduced, the shrinkage of concrete and filling materials will increase, and the electric flux and elastic modulus of concrete and filling materials will be affected.
[0003] The mainstream solution at this stage is to use sand and gravel aggregates with low clay content or process them to reduce the clay content, but this approach will increase construction costs and cause resource waste. Therefore, how to reasonably utilize clay minerals is a difficult problem in waste recycling. At the same time, as cement prices continue to rise, the proportion of enterprise filling costs in mining costs continues to increase. Therefore, finding a filling cementitious material suitable for replacing cement to reduce the cost of filling mining is an urgent problem to be solved in current filling mining. Summary of the invention
[0004] The object of the present invention is to provide a gelling material containing clay minerals to improve the strength of the clay mineral gel material.
[0005] The above purpose can be achieved by implementing the following technical solutions:
[0006] A cementitious material containing clay minerals, comprising the following components in parts by weight:
[0007] Clay mineral 55-60 parts;
[0008] 10-20 parts of flue gas desulfurization byproducts;
[0009] 10-20 parts of converter slag
[0010] Improver 5-10 parts;
[0011] The improver comprises the following components in parts by weight: 20-25 parts of calcium silicate, 10-25 parts of tricalcium aluminate, 1-5 parts of nano-alumina, 10-15 parts of tricalcium silicate, 5-15 parts of tetracalcium aluminoferrite, 2-6 parts of methyl polycarboxylic acid, and 1-5 parts of vinyl acetate.
[0012] Optionally, the clay mineral includes at least one of kaolinite clay mineral, montmorillonite clay mineral and illite clay mineral.
[0013] Optionally, the water-to-cement ratio of the cementitious material is 0.2-0.4.
[0014] Optionally, the mass fraction of the modifier in the gel material is 5-10%.
[0015] Optionally, the kaolinite clay mineral preferably includes the following components in parts by weight: by weight, 50-55 parts of SiO2, 32-41 parts of Al2O3, 1-4 parts of K2O, 0.1-1 parts of Fe2O3, 0.1-1 parts of MgO, 0.1-1 parts of CaO, 0-1 parts of Na2O and 0.1-1 parts of P2O5.
[0016] Optionally, the montmorillonite clay mineral preferably includes the following components in parts by weight: 60-72 parts of SiO2, 12-22 parts of Al2O3, 1-3 parts of K2O, 1-4 parts of Fe2O3, 3-6 parts of MgO, 3-6 parts of CaO, and 0-1 parts of Na2O.
[0017] Optionally, the illite clay mineral preferably includes the following components in parts by weight: 65-80 parts of SiO2, 12-20 parts of Al2O3, 3-8 parts of K2O, 1-3 parts of Fe2O3, 0.2-1 parts of MgO, 0.1-1 parts of CaO, and 1-2 parts of Na2O.
[0018] Optionally, the particle size of the kaolinite is above 200 mesh;
[0019] Preferably, the particle size of the kaolinite is 250-300 mesh.
[0020] Optionally, the particle size of the montmorillonite is above 900 mesh;
[0021] Preferably, the particle size of the montmorillonite is 1000-1200 mesh.
[0022] Optionally, the illite has a particle size of 600 mesh or more;
[0023] Preferably, the particle size of the illite is 700-1000 mesh.
[0024] By limiting the particle size of clay minerals, the difficulty of hydration can be reduced on the one hand, and the uniformity of the material can be improved on the other hand.
[0025] Optionally, the flue gas desulfurization byproduct includes the following components in parts by weight: 38-52 parts of CaO, 1-8 parts of SiO2, 0-3 parts of Al2O3, 0-3 parts of MgO, 30-52 parts of SO3, and 0-3 parts of Cl. Flue gas desulfurization byproduct refers to a solid sulfur byproduct produced by flue gas desulfurization.
[0026] Optionally, the steel slag is converter steel slag, comprising the following components in parts by weight: 15-25 parts of SiO2, 1-8 parts of MgO, 1-6 parts of Al2O3, 30-52 parts of CaO, 10-20 parts of Fe2O3, 0-3 parts of P2O5, and 0-3 parts of MnO.
[0027] The present invention also proposes the use of the above-mentioned cementitious material containing clay minerals in the preparation of cementitious cementitious materials.
[0028] According to the common knowledge in the art, the chemical composition of the clay mineral and desulfurization by-products described in the present invention refers to the content of various metals or mineral elements in the form of oxides, and does not refer to the content of compounds existing in the form of oxides in the clay mineral, slag or desulfurization by-products. In addition, the above chemical composition results can be obtained by conventional detection methods available in the art, such as typical fluorescence detection methods after or before burnout.
[0029] The technical solution of the invention has the following advantages:
[0030] Compared with the existing cement clinker or solid waste-based cementitious materials, the raw materials of the cementitious material containing clay minerals provided by the present invention are composed of clay minerals, desulfurization byproducts, steel slag and modifiers, without adding cement clinker and slag, which greatly reduces the cost of raw materials. Due to the synergistic effect of the components in the present invention, they can still show good cementing properties and rheological properties, including compressive strength and fluidity. According to GB17671-1999 "Test Method for Strength of Cement Mortar", the cementitious material of the present invention is prepared into a slurry test block with a size of 30mm×30mm×50mm. It is cured at a temperature of 20°C and a humidity of more than 99.5%, showing good compressive strength.
[0031] Compared with existing cementitious materials, the clay mineral of the present invention has a high proportion, which fully improves the utilization rate of clay minerals and reasonably solves the problem of clay mineral storage. The cementitious material containing clay minerals provided by the present invention stimulates the activity of clay minerals, making them useful components in concrete or filling systems, and maximizing the effectiveness of clay minerals. DETAILED DESCRIPTION
[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] The specific compositions of the clay minerals, steel slag and desulfurization by-products used in the examples and comparative examples are shown in Table 1. The improver was purchased from a certain environmental resources company.
[0037] Table 1 Chemical composition of raw materials
[0038]
[0039]
[0040] Example 1
[0041] The composition of the improved cementitious material containing clay minerals for curing at 25 degrees is as follows:
[0042] 58g kaolinite (particle size is 200 mesh), 16g steel slag, 16g desulfurization by-product, water-binder ratio is 0.3, and improver is 10g (including 3.2g calcium silicate, 2.5g tricalcium aluminate, 0.4g nano-alumina, 1.4g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0043] Example 2
[0044] The composition of the improved cementitious material containing clay minerals for curing at 55 degrees is as follows:
[0045] 58g kaolinite (200 mesh), 16g steel slag, 16g desulfurization by-product, water-binder ratio 0.3, 10g improver (including 3.2g calcium silicate, 2.5g tricalcium aluminate, 0.4g nano alumina, 1.4g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0046] Example 3
[0047] The composition of the improved cementitious material containing clay minerals for curing at 25 degrees is as follows:
[0048] 58g montmorillonite (900 mesh), 16g steel slag, 16g desulfurization by-product, water-binder ratio 0.3, 10g improver (including 3.1g calcium silicate, 2.3g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.6g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0049] Example 4
[0050] The composition of the improved cementitious material containing clay minerals for curing at 55 degrees is as follows:
[0051] 58g montmorillonite (900 mesh), 16g steel slag, 16g desulfurization by-product, water-binder ratio 0.3, 10g improver (including 3.1g calcium silicate, 2.3g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.6g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0052] Example 5
[0053] The composition of the improved cementitious material containing clay minerals for curing at 25 degrees is as follows:
[0054] 58g illite (particle size is 600 mesh), 16g steel slag, 16g desulfurization by-product, water-binder ratio is 0.3, and improver is 10g (including 3.2g calcium silicate, 2.4g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.4g vinyl acetate).
[0055] Example 6
[0056] The composition of the improved cementitious material containing clay minerals for curing at 55 degrees is as follows:
[0057] Illite 58g (600 mesh), steel slag 16g, desulfurization by-product 16g, water-binder ratio 0.3.
[0058] Improver 10g (including 3.2g calcium silicate, 2.4g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.4g vinyl acetate).
[0059] Comparative Example 1
[0060] The difference from Example 2 is that no steel slag is added, and the specific composition is as follows:
[0061] Curing at 55 degrees, the composition of the improved cementitious material containing clay minerals is as follows:
[0062] 65g kaolinite (200 mesh), 25g desulfurization by-product, water-binder ratio 0.3, 10g improver (including 3.2g calcium silicate, 2.5g tricalcium aluminate, 0.4g nano-alumina, 1.4g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0063] Comparative Example 2
[0064] The difference from Example 2 is that no desulfurization byproduct is added. The specific composition is as follows:
[0065] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0066] 65g kaolinite (200 mesh), 25g steel slag, water-binder ratio 0.3, 10g improver (including 3.2g calcium silicate, 2.5g tricalcium aluminate, 0.4g nano-alumina, 1.4g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0067] Comparative Example 3
[0068] The difference from Example 4 is that no steel slag is added, and the specific composition is as follows:
[0069] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0070] 65g montmorillonite (900 mesh), 25g desulfurization by-product, water-binder ratio 0.3, improver 10g (including 3.1g calcium silicate, 2.3g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.6g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0071] Comparative Example 4
[0072] The difference from Example 4 is that no desulfurization byproduct is added, and the specific composition is as follows:
[0073] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0074] 65g montmorillonite (900 mesh), 25g steel slag, water-binder ratio 0.3, 10g improver (including 3.1g calcium silicate, 2.3g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.6g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0075] Comparative Example 5
[0076] The difference from Example 6 is that no steel slag is added, and the specific composition is as follows:
[0077] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0078] 65g illite (600 mesh), 25g desulfurization by-product, water-binder ratio 0.3, improver 10g (including 3.2g calcium silicate, 2.4g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.4g vinyl acetate).
[0079] Comparative Example 6
[0080] The difference from Example 6 is that no desulfurization by-product is added. The specific composition is as follows:
[0081] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0082] 65g illite (600 mesh), 25g steel slag, water-binder ratio 0.3, 10g improver (including 3.2g calcium silicate, 2.4g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.4g vinyl acetate).
[0083] Comparative Example 7
[0084] The difference from Example 2 is that the overall dosage of the modifier is increased in proportion, and the specific composition is as follows:
[0085] Curing at 55 degrees, the composition of the improved cementitious material containing clay minerals is as follows:
[0086] 60g kaolinite (200 mesh), 12g steel slag, 12g desulfurization by-product, water-binder ratio 0.3, 16g improver (including 3.2g calcium silicate, 2.5g tricalcium aluminate, 0.4g nano-alumina, 1.4g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0087] Comparative Example 8
[0088] The difference from Example 4 is that the overall dosage of the modifier is increased in proportion, and the specific composition is as follows:
[0089] The composition of the improved cementitious material containing clay minerals for curing at 55 degrees is as follows:
[0090] 60g montmorillonite (900 mesh), 12g steel slag, 12g desulfurization by-product, water-binder ratio 0.3, 16g improver (including 3.1g calcium silicate, 2.3g tricalcium aluminate, 0.5g nano-alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.6g methyl polycarboxylic acid, and 0.5g vinyl acetate).
[0091] Comparative Example 9
[0092] The difference from Example 6 is that the overall dosage of the modifier is increased in proportion, and the specific composition is as follows:
[0093] The composition of the improved cementitious material containing clay minerals for curing at 55 degrees is as follows:
[0094] 60g illite (600 mesh), 12g steel slag, 12g desulfurization by-product, water-binder ratio 0.3, 16g improver (including 3.2g calcium silicate, 2.4g tricalcium aluminate, 0.5g nano alumina, 1.5g tricalcium silicate, 1.5g tetracalcium aluminoferrite, 0.5g methyl polycarboxylic acid, and 0.4g vinyl acetate).
[0095] Comparative Example 10
[0096] The difference from Example 1 is that no improver is added, and the specific composition is as follows:
[0097] Curing at 25 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0098] 60g kaolinite (particle size 200 mesh), 20g steel slag, 20g desulfurization by-product, water-binder ratio 0.25.
[0099] Comparative Example 11
[0100] The difference from Example 2 is that no improver is added, and the specific composition is as follows:
[0101] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0102] 60g kaolinite (200 mesh), 20g steel slag, 20g desulfurization by-product, water-binder ratio 0.25.
[0103] Comparative Example 12
[0104] The difference from Example 3 is that no improver is added, and the specific composition is as follows:
[0105] Curing at 25 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0106] Montmorillonite (900 mesh) 60g, steel slag 20g, desulfurization by-product 20g, water-binder ratio 0.25.
[0107] Comparative Example 13
[0108] The difference from Example 4 is that no improver is added, and the specific composition is as follows:
[0109] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0110] 60g montmorillonite (900 mesh), 20g steel slag, 20g desulfurization by-product, water-binder ratio 0.25.
[0111] Comparative Example 14
[0112] The difference from Example 5 is that no improver is added, and the specific composition is as follows:
[0113] Curing at 25 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0114] 60g illite (particle size 600 mesh), 20g steel slag, 20g desulfurization by-product, water-binder ratio 0.25.
[0115] Comparative Example 15
[0116] The difference from Example 6 is that no improver is added, and the specific composition is as follows:
[0117] Curing at 55 degrees, the composition of the cementitious material containing clay minerals is as follows:
[0118] Illite 60g (600 mesh), steel slag 20g, desulfurization by-product 20g, water-binder ratio 0.25.
[0119] Performance Testing
[0120] The cementitious materials of Examples 1 to 12 and Comparative Examples 1 to 9 were prepared into pure slurry samples according to GB17671-1999 "Test Method for Strength of Cement Mortar", with a sample size of 30mm×30mm×50mm, and cured at a temperature of 20°C and a humidity of more than 99.5%. After casting and molding, the compressive strength was tested at different ages. The compressive strength was tested according to the compressive strength test method specified in "GB / T17671-1999 Test Method for Strength of Cement Mortar (ISO Method)". The test results are shown in Table 2:
[0121] Table 2 Compressive strength of mortar test blocks
[0122]
[0123] As can be seen from Table 2, the improved cementitious material provided by the present invention can improve the compressive strength of kaolinite clay minerals, montmorillonite clay minerals and illite clay minerals, wherein the cementitious material containing kaolinite clay minerals and montmorillonite clay minerals has a compressive strength of more than 20 MPa at 28 days, and has use value (28-day strength ≥ 20 MPa), and after adding the modifier, the compressive strength is significantly enhanced compared to before adding. As can be seen from Comparative Examples 1 to 9, not adding steel slag or desulfurization byproduct cementitious materials has an effect on strength, and excessively increasing the amount of modifier does not improve strength. As can be seen from the comparison of Comparative Examples 10 to 15 with Examples 1 to 6, not adding the composite additive in this application will significantly reduce the strength.
[0124] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A cementitious material containing clay minerals, characterized in that: The composition comprises the following components in parts by weight: Clay mineral 55-60 parts; 10-20 parts of flue gas desulfurization byproducts; 10-20 parts of converter slag; Improver 5-10 parts; The improver comprises the following components in parts by weight: 20-25 parts of calcium silicate, 10-25 parts of tricalcium aluminate, 1-5 parts of nano-alumina, 10-15 parts of tricalcium silicate, 5-15 parts of tetracalcium aluminoferrite, 2-6 parts of methyl polycarboxylic acid, and 1-5 parts of vinyl acetate.
2. The clay mineral-containing cementitious material according to claim 1, characterized in that: The clay mineral includes at least one of kaolinite clay mineral, montmorillonite clay mineral and illite clay mineral.
3. The clay mineral-containing cementitious material according to claim 1, characterized in that: The water-to-cement ratio of the clay mineral-containing cementitious material is 0.2-0.
4.
4. The clay mineral-containing cementitious material according to claim 1, characterized in that: The mass fraction of the modifier in the clay mineral-containing gelling material is 5-10%.
5. The clay mineral-containing cementitious material according to claim 2, characterized in that: The particle size of the kaolinite is above 200 mesh; Preferably, the particle size of the kaolinite is 250-300 mesh.
6. The clay mineral-containing cementitious material according to claim 2, characterized in that: The particle size of the montmorillonite is above 900 mesh; Preferably, the particle size of the montmorillonite is 1000-1200 mesh.
7. The clay mineral-containing cementitious material according to claim 2, characterized in that: The illite has a particle size of 600 mesh or more; Preferably, the particle size of the illite is 700-1000 mesh.
8. The clay mineral-containing cementitious material according to claim 1, characterized in that: The flue gas desulfurization by-products include the following components in parts by weight: 38-52 parts of CaO, 1-8 parts of SiO2, 0-3 parts of Al2O3, 0-3 parts of MgO, 30-52 parts of SO3, and 0-3 parts of Cl.
9. The clay mineral-containing cementitious material according to claim 1, characterized in that: The steel slag is converter steel slag, and comprises the following components in parts by weight: 15-25 parts of SiO2, 1-8 parts of MgO, 1-6 parts of Al2O3, 30-52 parts of CaO, 10-20 parts of Fe2O3, 0-3 parts of P2O5, and 0-3 parts of MnO.
10. Use of the clay mineral-containing cementitious material according to any one of claims 1 to 9 in the preparation of cementitious cementitious materials.
